Self-Efficacy Mahasiswa Biologi Setelah Penerapan Model WE-ARe (Warm-up, Exploring, Argumentation, Resume). - Astuti Muh. Amin (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2022)
Strong self-efficacy can increase students’ sense of comfort and confidence in providing arguments. A preliminary study that was completed in 2020 offers an indication that typically, the average self-efficacy of Biology Tadris students at IAIN Ternate is in the poor group (43.37). The objective of this study was to identify Biology students’ self-efficacy after the implementation of WE-ARe (Warm-up, Exploring, Argumentation, Resume). A quantitative study design was used. The study population comprised of all Biology Tadris students at IAIN Ternate, North Maluku, whereas the research sample consisted of 50 fourth semester students from the same university. Data were collected using a self-efficacy questionnaire that was confirmed to be valid and reliable. Descriptive statistical analysis was performed to examine the participants’ self-efficacy by adding together the scores of all questionnaire items/statements. The results of the study and data analysis showed that the total self-efficacy score of biology students in WE-ARe classroom was in the "confident enough" group (mean 80.21). The WE-ARe learning model can improve student confidence and help create a good atmosphere in the classroom so that pupils acquire an optimistic attitude towards learning success. The steps of the WE-ARe model (Warm-up, Exploring, Argumentation, Resume) can stimulate the self-efficacy of students from the Department of Biology. This study is expected to contribute to the improvement of student learning motivation and the quality of instructional design that is focused on building student self-confidence. Keywords: Biology students, Model WE-ARe model, Implementation, Self-Efficacy.